2022
DOI: 10.1101/2022.06.23.497336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Antimicrobial Peptides Self-assemble as α/β Chameleon Amyloids

Abstract: Amyloid protein fibrils and some antimicrobial peptides (AMPs) share biophysical and structural properties. This observation suggests that ordered self-assembly can act as an AMP-regulating mechanism, and, vice versa, that human amyloids play a role in host defense against pathogens, as opposed to their common association with neurodegenerative and systemic diseases. Based on previous structural information on toxic amyloid peptides, we developed a sequence-based bioinformatics platform and, led by its predict… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…9,10 Recent cryoEM studies also identified cross-α fibril structures for a number of peptides. [11][12][13][14] The formation of peptide fibrils follows typical nucleation-elongation kinetics with a slow nucleation phase followed by a fast elongation and growth of the peptide oligomers into fibrillar aggregates (see Figure 1a). 15,16 Several studies suggested an α-helical peptide conformation as an intermediate toward β-sheet rich fibrils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Recent cryoEM studies also identified cross-α fibril structures for a number of peptides. [11][12][13][14] The formation of peptide fibrils follows typical nucleation-elongation kinetics with a slow nucleation phase followed by a fast elongation and growth of the peptide oligomers into fibrillar aggregates (see Figure 1a). 15,16 Several studies suggested an α-helical peptide conformation as an intermediate toward β-sheet rich fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recent cryoEM studies also identified cross-α fibril structures for a number of peptides. 1114…”
Section: Introductionmentioning
confidence: 99%